Wujud Sapaan “Anak” dalam Tindak Tutur Berbahasa Banjar - Rissari Yayuk (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2015)
This study is intended to describe form of greeting a child in Banjar-language speech acts that have not been investigated. in fact, through this study will be known to one of the cultural community of Banjar, especially in the family environment. Issues raised (1) how marker form greeting children Banjar language? and (2) how is the realization of children's use of language Banjar greeting speech act ?. Objectives to be achieved adalan to know (1) being marker Banjar language greeting children and (2) actual use of greeting children Banjar language in speech acts? This type of research is descriptive qualitative. Techniques used in data collection and documentation is recording technique. The study concluded Based on survey results revealed that the marker greeting child in Banjar consists of the Child or kid, Tung, Idang, Nang or Sam. Fourth greeting used by gender and there are not. Next, the realization of children's use of language Banjar greeting speech act consists of a directive speech act, expressive. commissive, assertive